Adventures in Small Tourism Studies and Stories - Scherf, Kathleen (Small Cities Sustainability Studies in Community and Cultural Engagement, 2023)
Adventures in Small Tourism presents academic studies and personal stories about small tourism. While small tourism is not new, it has become increasingly important as the widespread negative effects of overtourism have become increasingly apparent, with cities like Amsterdam and Barcelona experiencing barriocide, the death of neighbourhoods, as they host overwhelming numbers of visitors. Small tourism, especially creative tourism, not only reduces the actual and potential negative impact of guests on local culture but actively seeks to strengthen and revive local communities by weaving together the experiences of guest and host. Participatory, respectful, and celebratory methods and manners of tourism, rooted in community and cultural networks, has the potential to strengthen cultural bonds, support economic development, and increase sustainability. Focusing on the provision of small-scale creative tourism experiences, Adventures in Small Tourism explores possibilities for local empowerment through community-based tourism. With stories and studies from Italy, Portugal, Colombia, Japan, Australia, and beyond, this collection tells stories of visitors and residents coming together to co-create place in walks and workshops, gastronomy and art, festivals, markets, and more. This is a book that dares to ask what the future can be. With contributions by: Diana Guerra Amaya, Katja Bek Kos, Keith Lewis Bradbury, Nancy Duxbury, Darcen David Esau, Mohammadreza Gohari, John S. Hull, Vid Kmetič, Attila Komlós, Donald Lawrence, Sylvia M. Leighton, Alison Lullfitz, Moira A.L. Maley, Courtney W. Mason, Una McMahon-Beattie, Mateja Meh, Emese Panyik, Carol Pettersen, André Luis Quintino Principe, Meng Qu, Donna M. Senese, M. Jane Thompson, Spencer J. Toth, J. Eddy Wajon, Josie Vayro, Ian Yeoman, Simona Zollet, and Diana Marcela Zuluaga Guerra